Modelling of three phase induction machine using Simulink / Noor Hasnizam Hanafi - Hanafi, Noor Hasnizam (1999)
This thesis describes the simulation of three phase induction machines in the stationary reference frame using the SIMULINK software package of MATLAB. This model is based on two-axis theory of the stationary reference frame. The model uses the voltage source and mechanical torque as inputs and per unit speed and electromechanical torque as outputs. Simulation of the three-phase induction machine in the stationary reference frame can be used in the transient studies of adjustable-speed drives.